2018
DOI: 10.12965/jer.1836550.275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on mitochondrial hydrogen peroxide emission and calcium retention capacity in rat heart

Abstract: Aging is a risk factor for heart disease and heart failure, which result from a progressive impairment of cardiac functions, including stroke volume, cardiac output, blood flow, and oxygen consumption. Age-related cardiac dysfunction is associated with impaired cardiac structures, such as the loss of myocytes, structural remodeling, altered calcium (Ca2+) handling, and contractile dysfunction. However, the mechanism by which aging affects mitochondrial function in the heart is poorly understood. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…These signals eventually result in DNA fragmentation and programmed cell death [12,16,25]. We recently found increased mitochondrial hydrogen peroxide production with aging in rat cardiac muscles [5]. Interestingly, the current study revealed that the Bax/Bcl-2 ratio was markedly higher in the cardiac muscles of older rats, indicating that the aging phase was related to early-stage mitochondria-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…These signals eventually result in DNA fragmentation and programmed cell death [12,16,25]. We recently found increased mitochondrial hydrogen peroxide production with aging in rat cardiac muscles [5]. Interestingly, the current study revealed that the Bax/Bcl-2 ratio was markedly higher in the cardiac muscles of older rats, indicating that the aging phase was related to early-stage mitochondria-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 42%
“…Several studies suggested that mitochondria have evolved to regulate other cellular functions, including those contributing to biological aging, such as the generation of reactive oxygen species (ROS), inflammation, senescence, and resultant necrotic and apoptotic cell death [4]. Our studies have revealed that aging mainly results in damage to the electron transport chain during mitochondrial respiration, due to a decrease in electron transport by complex II-IV, which can promote electron leakage and ROS production [5].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Mitochondrial ROS is generated by products of the mitochondrial electron transfer chain during coupled respiration in complexes I and III [ 15 ]. ROS plays different biological roles depending on its concentration: (1) appropriate ROS is an essential mediator of cellular signaling and redox signals that are necessary for cellular homeostasis [ 16 ]; (2) a low level of ROS is needed for cellular differentiation, proliferation, growth, and adaptive responses [ 17 ]; (3) excessive ROS production induces both mitochondrial dysfunction and oxidative stress in proteins, nuclear DNA, mtDNA, and lipids [ 16 ]. In previous studies, regular exercise reduced ROS and elevated antioxidant enzymes in isolated heart mitochondria [ 10 ] and skeletal muscle [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, inhibition of mitochondrial Ca 2+ influx attenuated pro-arrhythmic activity in this model and reduced mitochondrial ROS emission. In pathophysiology, it would be rational to reduce mitochondrial Ca 2+ influx, despite some evidence that SR-mitochondria communication may be diminished in aging [58,63,155]. This reduction may be viewed as an adaptive mechanism to reduce mitochondrial [Ca 2+ ] and, thereby, limit deleterious mitochondrial ROS production in the senescent myocardium.…”
Section: Intracellular Ca2+ Homeostasis In the Aged Heartmentioning
confidence: 99%